Disaggregation and the Labor Productivity Index - Beebe, Jack H.; Haltmaier, Jane (The Review of Economics and Statistics, 1983)
States. Rather, observed interregional differences in average real wages probably arise from different relative endowments of various heterogeneous labor types. Because these results conflict with findings of most previous studies, comparisons are made with the approaches taken by other investigators. Those comparisons indicate that empirical estimates of interregional differences in the structure of wage and earnings equations are sensitive to (1) the treatment of geographic cost of living differences, (2) the completeness of the specification of the regressors, particularly the human capital measures, and (3) whether part-time workers are included in the sample.